Oral absorption characteristics and mechanisms of a pectin-type polysaccharide from Smilax china L. across the intestinal epithelium. (15th October 2021) - Zhang, Yu; Liu, Junxi; Dou, Pengfei; Wu, Zhijing; Zheng, Ziming; Pan, Xianglin; Zhou, Tao; Wang, Kaiping
Abstract: The elucidation of the oral absorption of natural polysaccharides contributes to their further research and utilization. Herein, to explore the absorption of a pectin-type polysaccharide from Smilax china L. (SCLP), SCLP was respectively fluorescently labeled with fluorescein-5-thioicarbazide (FSCLP) and Cyanine7 amine (Cy7-SCLP) for in vitro and in vivo tracking. The near-infrared imaging demonstrated that Cy7-SCLP was absorbable in the small intestine and distributed in the liver and kidney after oral administration. Subsequently, in vitro intestinal epithelial tissue experiments showed that the jejunum was the dominant site of FSCLP transport. Further transport studies in the Caco-2 cell monolayer illustrated that FSCLP was delivered across the monolayer via transcellular transport by caveolae-mediated endocytosis and macropinocytosis together with paracellular transport by reversibly affecting tight junctions. In summary, this work presents the oral absorption characteristics and mechanisms of SCLP through the intestinal epithelium, which will facilitate the further development of SCLP and pectin polysaccharides. Highlights: The oral absorption of SCLP was investigated to reveal the information about its oral pharmacokinetics. SCLP was achieved the in vitro and in vivo tracking by labeling with FTSC and Cy7 amine. SCLP could be absorbed through the small intestine and distributed in the liver and kidney. The jejunum played a dominant role in absorption of SCLP in the small intestine. SCLP could be transported across the Caco-2 cell monolayer via transcellular routes and paracellular routes.